Emergency logistics in large-scale disaster context: achievements and challenges - Jiang, Yiping; Yuan, Yufei; Huang, Kai; Zhao, Lindu; McMaster eBusiness Research Centre (MeRC) (My University, 2013)
Different from normal business operations, emergency response for large scale disaster is complex and there are many challenges arise. Research on emergency logistics is still in its infancy stage. Understanding the challenges and new research directions becomes imperative. In this paper, we present a literature review of emergency logistics in large-scale disaster context. First, we identify key characteristics of large-scale disasters and assess their challenges to emergency logistics. Second, we analyze and summarize current literatures on how to deal with these challenges. Finally, we discuss existing gaps in relevant research and suggest future research directions.
28 p. ; Includes bibliographical references. ; "June 2013."
Keywords: Large-scale disaster; Emergency response; Emergency logistics; Humanitarian logistics; Operations research